Answer:
Original length = 2.97 m
Explanation:
Let the original length of the pendulum be 'L' m
Given:
Acceleration due to gravity (g) = 9.8 m/s²
Original time period of the pendulum (T) = 3.45 s
Now, the length is shortened by 1.0 m. So, the new length is 1 m less than the original length.
New length of the pendulum is, ![L_1=L-1](https://tex.z-dn.net/?f=L_1%3DL-1)
New time period of the pendulum is, ![T_1=2.81\ s](https://tex.z-dn.net/?f=T_1%3D2.81%5C%20s)
We know that, the time period of a simple pendulum of length 'L' is given as:
-------------- (1)
So, for the new length, the time period is given as:
------------ (2)
Squaring both the equations and then dividing them, we get:
![\dfrac{T^2}{T_1^2}=\dfrac{(2\pi)^2\frac{L}{g}}{(2\pi)^2\frac{L_1}{g}}\\\\\\\dfrac{T^2}{T_1^2}=\dfrac{L}{L_1}\\\\\\L=\dfrac{T^2}{T_1^2}\times L_1](https://tex.z-dn.net/?f=%5Cdfrac%7BT%5E2%7D%7BT_1%5E2%7D%3D%5Cdfrac%7B%282%5Cpi%29%5E2%5Cfrac%7BL%7D%7Bg%7D%7D%7B%282%5Cpi%29%5E2%5Cfrac%7BL_1%7D%7Bg%7D%7D%5C%5C%5C%5C%5C%5C%5Cdfrac%7BT%5E2%7D%7BT_1%5E2%7D%3D%5Cdfrac%7BL%7D%7BL_1%7D%5C%5C%5C%5C%5C%5CL%3D%5Cdfrac%7BT%5E2%7D%7BT_1%5E2%7D%5Ctimes%20L_1)
Now, plug in the given values and calculate 'L'. This gives,
![L=\frac{3.45^2}{2.81^2}\times (L-1)\\\\L=1.507L-1.507\\\\L-1.507L=-1.507\\\\-0.507L=-1.507\\\\L=\frac{-1.507}{-0.507}=2.97\ m](https://tex.z-dn.net/?f=L%3D%5Cfrac%7B3.45%5E2%7D%7B2.81%5E2%7D%5Ctimes%20%28L-1%29%5C%5C%5C%5CL%3D1.507L-1.507%5C%5C%5C%5CL-1.507L%3D-1.507%5C%5C%5C%5C-0.507L%3D-1.507%5C%5C%5C%5CL%3D%5Cfrac%7B-1.507%7D%7B-0.507%7D%3D2.97%5C%20m)
Therefore, the original length of the simple pendulum is 2.97 m